The rise of the modern company in East-Central Europe - Veress , Emőd (Joint Stock and Limited Liability Companies in East Central Europe, 2025)
References:Anđelković, N. (2020) ‘Tito i Jugoslavija: Nacionalizacija privatne imovine - talasi koji i dalje zapljuskuju’, BBC, 7 December [Online]. Available at: https://www.bbc.com/serbian/lat/balkan-55159029h (Accessed: 10 October 2025).Auer, Á. (2016) ‘A diszpozitivitás jelentősége a társasági jogban’, Magyar Jog, 2016/7–8, pp. 395–404.Auer, Á., Papp, T. (2023) ‘The Mandatory and Default Regulation in Hungarian Company Law – A Decade of Experience’, European Company and Financial Law Review, 20(2), pp. 314–335 [Online]. Available at: https://www.degruyterbrill.com/document/doi/10.1515/ecfr-2023-0012/html (Accessed: 10 October 2025).Balogh, E. (2011) ‘Császár Ferenc szerepe a magyar váltójog kifejlődésében’, Jogtorteneti Szemle, (2), pp. 1–9.Bałtruszajtys, G. (1959) ‘Kompanie akcyjne w Polsce w drugiej połowie XVIII w.: Z zagadnień początków prawa akcyjnego’, Czasopismo Prawno-Historyczne, 11(2), pp. 77–128.Barbić, J. (2006) Pravo društava: Knjiga prva, Opći dio. Zagreb: Organizator.Botos, J. (1991) A Pesti Magyar Kereskedelmi Bank tortenete. Budapest: Kereskedelmi Bank Rt.Černá, S., Štenglová, I., Pelikánová, I. et al. (2021) Pravo obchodnich korporaci, 2nd edn. Praha: Wolters Kluwer.Codex Cambio Mercantilis Pro Regno Hungaria Partibusque Eidem Adnexis In Tres Partes Divisus Per Regnicolarem Juridicam Deputationem Articulo 67. 1791. ordinatam elaborate (1802) Posonii, typis Franc. Jos. Patzko.Csehi, Z. (2016) ‘Az új Ptk. jogi személy szabályozásának a kógenciájáról és diszpozitivitásáról’, Polgari Jog, 3(3), pp. 1–8.Dąbrowska, J. (2020) ‘O początkach spółki akcyjnej’, Zeszyty Prawnicze, 19(4), 7–48 [Online]. Available at: https://czasopisma.uksw.edu.pl/index.php/zp/article/view/5451 (Accessed: 10 October 2025).Eichlerová, K. (2023) ‘Zvláštní právní formy obchodních korporací: existují, nebo ne?’, Obchodněpravni revue, (4) [Online]. Available at: https://app.beck-online.cz/bo/chapterview-document.seam?documentId=nrptembsgnpw64s7grpxgxzsgi4q (Accessed: 10 October 2025).Fegyveresi, Zs. (2017) ‘The Persistence of some characteristics of commercial law in the monist Romanian civil law’ in Menyhárd, A., Veress, E. (eds.) New civil codes in Hungary and Romania. Cham: Springer, pp. 35–42 [Online]. Available at: https://doi.org/10.1007/978-3-319-63327-5_4 (Accessed: 10 October 2025).FinStat (n.d.) [Online]. Available at: https://finstat.sk/ (Accessed: 10 October 2025).Frąckowiak, J. (2015) ‘Osiemdziesiąt lat polskiego prawa handlowego - wzloty, upadki oraz mozolna reaktywacja’, Acta Universitatis Wratislaviensis. Przegląd Prawa i Administracji, 2015/101, pp. 45–62.Fundárek, J. (1926) Obchodny zakon platny na Slovensku a v Podkarpatskej Rusi (Zák. čl. XXXVII z roku 1875). Bratislava: Právnická jednota.Gábriš, T. (2011) ‘Právne dejiny a obchodné právo: subjektívny alebo objektívny systém práva?’, Acta Facultatis Iuridicae Universitatis Comenianae. Bratislava: Univerzita Komenského v Bratislave, pp. 89–108.Gábriš, T., Janáč, V. (2022) ‘Shareholder and the company. Three centuries of evolution’, Pravny obzor, 2022/105 (special issue), pp. 14–28.Golštajn, A. (1967) Privredno ugovorno pravo. Zagreb: Informator.Górnicki, L. (2015) ‘Przewodnie konstrukcje i pojęcia kodeksu handlowego z 1934 roku’, Acta Universitatis Wratislaviensis. Prawo, 2015/101, pp. 63–91.Havel, B., Lasák, J., Pihera, V., Štenglová, I. (2023) ‘Czech Corporate Governance in the Light of its History and the Influence of the G20/OECD Corporate Governance Principle’, European Business Organization Review, 24(1), pp. 167–200.Hermann-Otavský, K. (1929) Všeobecny zakonik obchodni, a pozdějši normy obchodniho prava v zemich historickych. Praha: Nákladem “Československého kompasu”.Holbesz, A. (1939) A magyar hitelszervezet tortenete. Budapest: May János Nyomdai Műintézet.Horváth, A. (2005) A reszvenytarsasagok es a reszvenytarsasagi jog kialakulasa Magyarorszagon. Budapest: Rejtjel.Horváth, A. (2018) ‘A kereskedelmi törvény – 1875. évi XXXVII. tc.’ in Máthé, G.,Menyhárd, A., Mezey, B. (eds.) A kettős monarchia. Budapest: ELTE Eötvös, pp. 203–245.Hryniewiecki, J. (1939) Krotki zarys prawa handlowego obowiązującego w Polsce. Cz. 1: Kodeks handlowy. Poznań: W. Wilak. (Popularna Biblioteczka Prawnicza, z. 8a).Husár, J. (2017) ‘Zákonný článok XXXVII/1875 a jeho vplyv na vývoj slovenského obchodného práva’, Pravny obzor, 100(1), pp. 38–58.Ivanjko, Š. (1977) Samoupravna organiziranost združenega dela. Ljubljana: Zveza delavskih univerz Slovenije.Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba.Ivkošić, M. (2020) ‘Društvo s ograničenom odgovornošću u svjetlu novele Zakona o trgovačkim društvima iz 2019.’, Zbornik radova Pravnog fakulteta u Splitu, 57(2), pp. 551–583 [Online]. Available at: https://hrcak.srce.hr/237910 (Accessed: 10 October 2025).Jevremović-Petrović, T. (2021) ‘Elektronska registracija osnivanja privrednih društava u Republici Srbiji’, Pravo i privreda, 59(3), pp. 305–321 [Online]. Available at: https://doi.org/10.5937/PiP2103305J (Accessed: 10 October 2025).Jójárt, E. (2014) ‘Diszpozitivitás a régi és az új Polgári Törvénykönyvben – elméleti alapvetés’, Magyar Jog, 2014/12, pp. 673–685.Jovanović, N., Radović, V., Radović, M. (2021) Kompanijsko pravo – Pravo privrednih društava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje.Karmán, J., Pecháček, J. (1926) Slovensky obchodny zakon a predpisy ho doplňujuce s judikaturou najvyššieho sudu, ako i byv. uh. kurie a sudnych tabul. Praha: Nákladem Československého Kompasu.Kuklík, J. (2010) Znarodněne Československo. Od znarodněni k privatizaci – statni zasahy do vlastnickych a dalšich prav v Československu a jinde v Evropě. Praha: Auditorium.Lamotte, K. (1941) A Pesti Magyar Kereskedelmi Bank 1841–1941 – Szaz esztendő emlekei. Budapest.Luetić, J. (1982) ‘Osiguravajuća društva u Dubrovačkoj Republici 1794–1804.’, Anali Zavoda za povijesne znanosti HAZU u Dubrovniku, 20, pp. 189–208.Lupán, E. (1986) ‘AZ RKP felfogása az össznépi tulajdonról és a tulajdonjogról’, Korunk, (3).Lupán, E. (1988a) ‘Kié a föld? I’, Korunk, 47(5). pp. 330–334.Lupán, E. (1988b) ‘Kié a föld? II’, Korunk, 47(6). pp. 417–421. Malovský-Wenig, A. (1947) Přiručka obchodniho prava. Praha: Kompas.Margetić, L. (1997) Srednjovjekovno hrvatsko pravo: Obvezno pravo. Zagreb–Rijeka: Pravni fakultet Sveučilišta u Rijeci.Marković, L. (1914) Trgovački zakonik. Beograd: Geca Kon.Mićović, M. (2016) Privredno pravo, 4th edn. Kragujevac: Pravni fakultet u Kragujevcu, Institut za pravne i društvene nauke.Ministry of Justice of the Slovak Republic (2021) Legislativny zamer rekodifikacie prava obchodnych spoločnosti [Legislative intent for the recodification of corporate law] [Online]. Available at: https://www.justice.gov.sk/dokumenty/2022/02/Legislativny-zamer-ZoOSaS_2021.pdf (Accessed: 10 October 2025).Mirković, Z. (2019) Srpska pravna istorija, 3rd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje.Morawski, W. (n.d.) ‘W cieniu wzorów radzieckich (gospodarka Polski Ludowej – 1944–1956)’, ‘Biogramy.pl’ Filmoteka Narodowa – Instytut Audiowizualny [Online]. Available at: https://www.biogramy.pl/a/artykul/w-cieniu-wzorow-radzieckichgospodarka-polski-ludowej-1944-1956 (Accessed: 10 October 2025).Mrázová, Ž., Cukerová, D. (2023) ‘How the digitalisation has changed the Slovak company law: Implemention of the Directive 2019/1151 (Digitalisation Directive) and what next?’, EU and Comparative Law Issues and Challenges Series (ECLIC), 2023/7, [Online]. Available at: https://doi.org/10.25234/eclic/27454 (Accessed: 10 October 2025)Mrázová, Ž., (2021) ‘Vznik Spoločnosti A Družstva’ in Patakyová, M., Ďurica, M., Husár, J. et al. (eds) Aplikovane pravo obchodnych spoločnosti a družstva – ťažiskove inštituty. Bratislava: Wolters Kluwer SR.Nazaruk, P. (2014) ‘Analiza historyczno-prawna rozwoju instytucji spółki z ograniczoną odpowiedzialnością w Europie Zachodniej i Polsce’, Studia Gdańskie. Wizje i Rzeczywistość, 11, pp. 389–401.Nędzyński, S. (2021) ‘Prosta spółka akcyjna jako remedium na problemy polskich start-upów’, Zeszyt Prawniczy UAM, 11, pp. 233–248 [Online]. Available at: https://doi.org/10.14746/zpuam.2021.11.15 (Accessed: 10 October 2025). Osnova obchodniho zakona (1937). Praha: Ministerstvo spravedlnosti.Papp, T. (2010) ‘Társasági jogalkotásunk rövid története, európai kitekintéssel’ inNótári, T. (ed.) Unnepi tanulmanyok Sarkozy Tamas 70. szuletesnapjara. Szeged: Lectum.Patakyová, M. et al. (2020) ‘Slovak Simple Joint Stock Company – Critical Review and Preliminary Assessment’, European Company and Financial Law Review, 17(2), pp. 205–230.Pázmándi, K. (2023) ‘A diszpozitivitás diadala – a korlátolt felelősségű társaság szabályainak modernizálásáról’ in Tőkey, B. (ed.) Liber Amicorum – Unnepi tanulmanyok Kisfaludi Andras 65. szuletesnapjara. Budapest: Wolters Kluwer Hungary, pp. 153–161.Pókecz Kovács, A. (2011) ‘Schaffung der Handelsgesetze von 1840 durch die ungarische Nationalversammlung und deren Anwendung bis 1849’, Jura, 17(1), pp. 117–127.Pólya, J. (1892) A Pesti Magyar Kereskedelmi Bank keletkezesenek es otveneves fennallasanak tortenete. Budapest: Kertész József nyomása.Roller, M. (ed.) (1952) A Roman Nepkoztarsasag tortenete. Bukarest: Állami Tanügyi és Pedagógiai Kiadó.Sárközi, Z. (1988) ‘A kereskedelmi jogalkotás kezdetei és a részvénytársasági törvény kialakulása Magyarországon’, Jogtudomanyi Kozlony, 43(9), pp. 524–528.Sárközy, T. (1997) ‘A privatizáció modelljei Közép-Kelet-Európában’, Historia, (Millenial supplement), 1997/1.Sárközy, T. (2007) A szocializmus, a rendszervaltas es az ujkapitalizmus gazdasagi civiljoga 1945–2005. Budapest: HVGOrac.Sárközy, T. (2015) ‘Még egyszer a Ptk. jogi személy könyve állítólagos diszpozitivitásáról’, Gazdasag es Jog, 23(11), pp. 8–14.Savas, E. S. (1993) Privatizacio: Hogyan vonuljon ki az allam a gazdasagbol? Budapest: Akadémiai Kiadó.Škerlj, M. (ed.) (1938) Trgovinski zakon kraljevine Jugoslavije. Merkur: Belgrade.Sołtysiński, S. (1998) Kodeks handlowy. Komentarz. Tom II. Warszawa: C.H. Beck.Sorensen, K. E., Neville, M. (2014) ‘Social Enterprises: How Should Company Law Balance Flexibility and Credibility?’, European Business Organization Law Review, 15(2), pp. 267–308.Stražnicky, M. (1920) Predavanja iz trgovačkog prava. Zagreb: Tiskara Merkur.Suchoža, J. et al. (2009) Obchodné právo. Bratislava: Iura Edition.Suchoža, J. et al. (2011) Česko-slovenske kontexty obchodniho prava. Praha: Wolters Kluwer ČR.Šuleková, Ž. (2016) ‘Jednoduchá spoločnosť na akcie – nová forma obchodnej spoločnosti’, Sukromne pravo, 2(6), pp. 2–10.Vasiljević, M. (2012) Kompanijsko pravo – pravo privrednih društava, 7th edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje.Vékás, L. (2018) ‘A diszpozitív szabályozás elve és az elv kérdőjelei a gyakorlatban’, Magyar Jog, (7–8), pp. 385–391.Veress, E. (2015) ‘From Capitalism to Utopia: Communist nationalization of companies in Central and Eastern Europe’, Acta Universitatis Sapientiae, Legal Studies, 2015/1, pp. 125–137.Veress, E. (2017) ‘The new Romanian Civil Code – difficulties in the transition towards a monist private law’ in Menyhárd, A., Veress, E. (eds.) New civil codes in Hungary and Romania. Cham: Springer, pp. 27–34.Veress, E. (2018) ‘A részvénytársaság a magyar jogtörténetben’, Acta Universitatis Sapientiae, Legal Studies, 7(2), pp. 321–338.Veress, E. (2019) ‘Report from Hungary: Is It Possible to Issue Bearer Shares in Hungary? Remarks on Mandatory and Default Rules in Hungarian Company Law’, European Company Law, 16(3), pp. 95–100.Veress, E. (2020) ‘Regulation of joint-stock companies in 19th century Hungary’, Lex et Scientia, 27(1), pp. 123–138.Veress, E. (2021) ‘A szovjet típusú diktatúrák államosításai Kelet-Közép-Európában: értelmezési keretek’ in Mezey, B. (ed.) Kolcsonhatasok. Europa es Magyarorszag a jogtortenelem sodrasaban. Budapest: Gondolat Kiadó, pp. 332–350.Veress, E. (2023) ‘A társasági jog kialakulása és fejlődése’ in Fegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris, pp. 13–64.Vezekényi, U. (2020) ‘A diszpozitivitás és kógencia kérdésköre a társasági jogi szabályozásban’, Gazdasag es Jog, (11–12), pp. 44–47.